2018
DOI: 10.1021/acs.jpcc.8b08965
|View full text |Cite
|
Sign up to set email alerts
|

Spin–Orbit Charge Recombination Intersystem Crossing in Phenothiazine–Anthracene Compact Dyads: Effect of Molecular Conformation on Electronic Coupling, Electronic Transitions, and Electron Spin Polarizations of the Triplet States

Abstract: Phenothiazine (PTZ)–anthracene (An) compact electron donor/acceptor dyads were synthesized. The molecular conformation was constrained by rotation restriction to achieve an orthogonal geometry between the electron donor (PTZ) and the electron acceptor (An), with the aim to enhance the spin–orbit charge-transfer intersystem crossing (SOCT–ISC). The substitution positions on the PTZ and An moieties were varied to attain dyads with different mutual orientations of the donor/acceptor as well as different rotation-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 105 publications
6
97
1
Order By: Relevance
“…The authors show a generic scheme for triplet formation in donor-acceptor dyads (Fig. 9) that complies to the work of El-Sayed in 1974, 40 the work of Van Willigen, 24 Wasielewski, 23,37,41 and Filatov, Senge 29,31,35 and Buck et al 39 According to the authors, the recent studies conducted by Filatov et al, 29,31,35 Zhao et al, 30,34,36 lack magnetic field effects (MFE) measurements clearly indicating that SOCT-ISC is the main transition to populate triplet excited states. Buck et al proceeded to carry out studies to answer one question: in relation to Fig.…”
Section: Perspectivesupporting
confidence: 70%
See 2 more Smart Citations
“…The authors show a generic scheme for triplet formation in donor-acceptor dyads (Fig. 9) that complies to the work of El-Sayed in 1974, 40 the work of Van Willigen, 24 Wasielewski, 23,37,41 and Filatov, Senge 29,31,35 and Buck et al 39 According to the authors, the recent studies conducted by Filatov et al, 29,31,35 Zhao et al, 30,34,36 lack magnetic field effects (MFE) measurements clearly indicating that SOCT-ISC is the main transition to populate triplet excited states. Buck et al proceeded to carry out studies to answer one question: in relation to Fig.…”
Section: Perspectivesupporting
confidence: 70%
“…Using DFT calculations, they explained that the alkyl groups increased the S CT and reduced the electron accepting ability of the BODIPY moiety. Hou et al 36 synthesized phenothiazine(PTZ)-anthracene (An) dyads ( Fig. 8) with the aim of achieving orthogonal geometry thus enhancing SOCT-ISC.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The 1,7‐methyl groups on the boron dipyrromethene (Bodipy) moiety play a similar role in Bodipy‐derived electron donor/acceptor dyads showing SOCT‐ISC . We found that the presence of peri ‐H(C) of electron donor phenothiazine is helpful for conformation restriction . However, in all these molecular structural motifs, rotation about the C−C or the C−N linker is not fully restricted, and various conformations are still accessible with thermal energy.…”
Section: Introductionmentioning
confidence: 97%
“…[22][23][24][25][26] We found that the presence of peri-H(C) of electron donor phenothiazine is helpful for conformation restriction. [24,27,28] However,i na ll these molecular structural motifs, rotation about the CÀCo rt he CÀNl inker is not fully restricted, and various conformationsa re still accessible with thermale nergy.D eviation from the orthogonal geometry may be detrimental to the SOCT-ISC efficiency.T hus, fully rigid linkers are desired for linking the electron donora nd acceptor in these dyads, but this kind of linker is difficult to obtain from the point of view of synthesis.…”
Section: Introductionmentioning
confidence: 99%